Logical Fallacies in Tweets: A Case of Pakistani Political Discourse - Akram, Nadeem; Nousheen, Saba; Tabassum, Aleesha (Annals of Human and Social Sciences, 2022)
This qualitative descriptive work anticipates inspiring the users of social media to apply their critical thinking abilities to fairly assess the merits and defects of opinions. The researchers aim to inspire the user of social media to use responsible approach against their debates by pointing out and identifying the fallacies by its type to educate them. Researchers will point out diversity of fallacies with the help of examples. The findings of this study consequently have pedagogical implementations for practical uses to recognize logical fallacies in daily life. The research concludes that current political discussions are merely deceptive. They engage in emotional demagoguery, aggressive language, and personal attacks that have no place in a democracy. A reasonable, humble, and independent climate is needed to be re-established into the political sphere, and most importantly, citizens need to be made aware of these fallacies.